Cholangiocarcinoma following external beam radiotherapy: A report of two cases - Kulkarni, Anisha (Oncol Lett, 2017)
Cholangiocarcinoma (CCA) is a relatively rare primary malignancy, with established risk factors that include primary sclerosing cholangitis, choledochal cysts and hepatolithiasis. In the present study, two cases of CCA, which occurred following abdominal external beam radiotherapy (EBRT) for non-Hodgkin's lymphoma, are reported. Case 1 and 2 were diagnosed with cholangiocarcinoma 30 and 4 years following treatment with combined chemotherapy and abdominal radiotherapy treatment, respectively. The patients received chemotherapy as treatment of cholangiocarcinoma; however, whilst their symptoms improved, they succumbed within 12 and 2 months respectively following the diagnosis with cholangiocarcinoma. Currently, the association between radiation exposure and hepatobiliary malignancy remains unclear, however, we hypothesize that biliary epithelium sensitivity to ionizing radiation may have contributed to the etiology of the secondary malignancies observed in these two patients. This study indicates that patients treated with abdominal EBRT may benefit from a heightened index of suspicion and more intensive surveillance for secondary biliary malignancies.